2018
DOI: 10.1016/j.molmet.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α functions as a co-suppressor of XBP1s to regulate glucose metabolism

Abstract: ObjectivePeroxisome proliferator-activated receptor γ (PPARγ) coactivator-1α (PGC-1α) promotes hepatic gluconeogenesis by activating HNF4α and FoxO1. PGC-1α expression in the liver is highly elevated in obese and diabetic conditions, leading to increased hepatic glucose production. We previously showed that the spliced form of X-box binding protein 1 (XBP1s) suppresses FoxO1 activity and hepatic gluconeogenesis. The shared role of PGC-1α and XBP1s in regulating FoxO1 activity and gluconeogenesis led us to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…Although Mediator has been shown to play many roles in transcription (Allen and Taatjes 2015), the mechanism by which PGC-1α binding to MED1 promotes gene transcription is unclear. In addition to its transcriptional coactivator function, PGC-1α acts as a transcriptional repressor, as illustrated by its binding to and inhibition of the transcription factor XBP1s (Lee et al 2018), and also as an alternative splicing factor (Monsalve et al 2000;Martínez-Redondo et al 2016).…”
Section: The Cbp80-binding Motif Of Pgc-1 Proteinsmentioning
confidence: 99%
“…Although Mediator has been shown to play many roles in transcription (Allen and Taatjes 2015), the mechanism by which PGC-1α binding to MED1 promotes gene transcription is unclear. In addition to its transcriptional coactivator function, PGC-1α acts as a transcriptional repressor, as illustrated by its binding to and inhibition of the transcription factor XBP1s (Lee et al 2018), and also as an alternative splicing factor (Monsalve et al 2000;Martínez-Redondo et al 2016).…”
Section: The Cbp80-binding Motif Of Pgc-1 Proteinsmentioning
confidence: 99%
“…But up‐regulated FOXO1 was accompanied by a reduction of PGC‐1α, while PGC‐1α overexpression suppressed the activation of FOXO1 and FOXO3 in muscle (Kang & Ji, ). Hepatic PGC‐1α facilitated gluconeogenesis through multiple pathways served as a co‐activator for FOXO1 (Lee et al, ). Here, our results showed that elevated FOXO1 reduced PGC‐1α mRNA and protein levels, while FOXO1 inhibition increased transcription of PGC‐1α both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The XBP1s protein is known to be unstable (Calfon et al 2002); however, the underlying mechanism remains poorly understood. A recent study suggested that PGC1α represses XBP1s protein level in the liver by promoting its ubiquitination and degradation (Lee et al 2018). Interestingly, this study mapped amino acid residues 227-252 of XBP1s as required for its interaction with PGC1α (Lee et al 2018), distinct from residues 301-371, which are required to interact with SHP.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that PGC1α represses XBP1s protein level in the liver by promoting its ubiquitination and degradation (Lee et al 2018). Interestingly, this study mapped amino acid residues 227-252 of XBP1s as required for its interaction with PGC1α (Lee et al 2018), distinct from residues 301-371, which are required to interact with SHP. Very recently, another study showed that XBP1s ubiquitination and protein stability in natural killer cells are modulated in response to interleukin-15 signaling (Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%